Bakteri Penyebab Gingivitis dan Sensitivitas Antibiotik Pada Pasien Diabetes Melitus - Endriani, Rita; Rafni, Elita; Nabila, Hanifah Farah; Berlianti, Monica Putri; Alhadi, Dio Arif (Fakultas Kedokteran Universitas Riau, 2024)
Gingivitis is an inflammation of the gingiva caused by plaque and poor oral hygiene, including in patients with long-term diabetes mellitus and uncontrolled blood glucose. Gingivitis is caused by various bacteria such as Streptococcus sp, Staphylococcus aureus, Enterococcus faecalis, Streptococcus pneumoniae, Streptococcus pyogenes, Neisseria meningitidis and also the Enterobacteriaceae family, Haemophilus influenzae and Actinomycetes. Management of infection with antibiotics, especially beta-lactam class. The study aimed to determine the characteristics of the research subjects, the type of bacteria, and their sensitivity to the bacteria that cause gingivitis in diabetes mellitus (DM) patients. The research was a cross-sectional descriptive study at the internal medicine polyclinic at Arifin Achmad Hospital, Riau Province, and the Microbiology Laboratory of Medical Faculty, Universitas Riau. The research sample was a gingivitis plaque swab in DM patients who signed an informed consent. Samples were cultured, identified, and tested for antibiotic sensitivity. The results of the study obtained 34 samples with characteristics aged 33-67 years, most of them were women, high school education/equivalent, civil servants/army/police/retired. Most aerobic bacteria Klebsiella sp. The highest sensitivity to levofloxacin, amikacin, ciprofloxacin, trimethoprim-sulfamethoxazole, and meropenem, the lowest sensitivity to amoxicillin, ceftazidim, and amoxicillin-clavulanic acid.